"Extracellular matrix remodelling in the liver of rats subjected to dietary choline deprivation and/or thioacetamide administration". (22nd August 2018) - Al‐Humadi, Hussam; Alhumadi, Ahmed; Al‐Saigh, Rafal; Strilakou, Athina; Lazaris, Andreas C; Gazouli, Maria; Liapi, Charis
Summary: Choline deprivation is a recognized experimental approach to nonalcoholic steatohepatitis, while thioacetamide (TAA)‐induced liver fibrosis resembles alcoholic liver fibrogenesis. In order to elucidate the effect of TAA on liver extracellular matrix composition under choline deprivation due to choline‐deficient diet (CDD) administration, we evaluated the transcriptional and immunohistochemical (IHC) pattern of major hepatic matrix metalloproteinases (namely, MMP‐2, ‐9) and their tissue inhibitors (TIMP‐1, ‐2) in adult male albino Wistar rats at 30, 60 and 90 days. In the CDD+TAA group, IHC showed an early progressive increase in MMP‐2 expression, while MMP‐9 initially exhibited a significant increase followed by a gradual decrease; TIMP‐1 and TIMP‐2 IHC expressions showed gradual increase throughout the experiment. The MMPs‐TIMPs regulation at the transcriptional level was found to be increased in all groups throughout the experiment. The increased MMP‐2/TIMP‐2 and suppressed MMP‐9/TIMP‐1 ratios in IHC and in real‐time polymerase chain reaction (RT‐PCR) seemed to correlate with the degree of liver fibrosis. These results support the important role of MMPs and TIMPs in controlling the hepatic pathogenesis and shed more light on the recently described experimental approach to liver disease (steatohepatitis) under the impact of two insults (TAA and CDD).